The relationship between ethnic background and the use of restrictive practices to manage incidents of violence or aggression in psychiatric inpatient settings. (27th June 2021) - Payne‐Gill, James; Whitfield, Corin; Beck, Alison
Abstract: Restrictive practices raise considerable concern in mental health inpatient care. Previous studies suggest there are disparities in the use of restrictive practices to manage service users of different ethnic groups. The present study analyses the relationship between ethnicity and the use of restrictive practices to manage incidents of violence or aggression in inpatient settings across an NHS Mental Health Trust. Three years' worth of routinely collected incident data were analysed using multilevel multiple logistic regression to assess the relationship between ethnic group and four types of restrictive practices: physical restraint (without prone), physical restraint (with prone), seclusion, and rapid tranquilization. We controlled for a range of demographic variables and the type and severity of the incident. Adjusted analyses showed that service users with a Black African [Odds Ratio = 1.96, 95% CI: 1.36–2.83, P < 0.001], Black Caribbean [Odds Ratio = 1.76, 95% CI: 1.08–2.85, P = 0.022], Black Other [Odds Ratio = 1.76, 95% CI: 1.27–2.44, P = 0.001], and Mixed [Odds Ratio = 1.88, 95% CI: 1.11–3.18, P = 0.019] ethnic background were more likely to be secluded, and Black Caribbean [Odds Ratio = 1.45, 95% CI: 1.02–2.07, P = 0.040] service users were more likely to be restrained in prone position. We did not detect differences in the use of physical restraints without prone or in the use of rapid tranquilization. Our findings illustrate the need to focus on outcomes for different ethnic groups when implementing restraint reduction programmes.